2009
DOI: 10.1002/wnan.38
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐eluting stent coatings

Abstract: This paper reviews the development of coronary stents from a polymer scientist's view point, and presents the first results of an interdisciplinary team assembled for the development of new stent systems. Poly(styrene-b-isobutylene-b-styrene) block copolymer (SIBS), a nanostructured thermoplastic elastomer, is used in clinical practice as the drug-eluting polymeric coating on the Taxus coronary stent (trademark of Boston Scientific Co.). Our group has been developing new architectures comprising of arborescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 59 publications
2
55
0
1
Order By: Relevance
“…Butyl rubber (copolymer of isobutylene with a small fraction of isoprene) is by one order of magnitude less permeable to small molecules than other elastomers. 32,42 Butyl rubbers have long been used to make inner linings of tires 42 , medical gloves 43 , and drug-eluting stents 44 . Recently, butyl rubbers have been used as hermetic seals for stretchable electronics [45][46] .…”
Section: Coat and Humectantmentioning
confidence: 99%
“…Butyl rubber (copolymer of isobutylene with a small fraction of isoprene) is by one order of magnitude less permeable to small molecules than other elastomers. 32,42 Butyl rubbers have long been used to make inner linings of tires 42 , medical gloves 43 , and drug-eluting stents 44 . Recently, butyl rubbers have been used as hermetic seals for stretchable electronics [45][46] .…”
Section: Coat and Humectantmentioning
confidence: 99%
“…Instead, the few observed cells grew in clusters, indicative of their preference for one another compared to the surface. By counting the number of cells per mm 2 , it was found that there was no significant difference in the number of cells found on glass versus butyl rubber. However, 120-fold fewer cells were observed on PIB-PTX-COOH and 260-fold fewer on PIB-PS-PTX-COOH relative to butyl rubber.…”
Section: Articlementioning
confidence: 96%
“…A triblock copolymer of polystyrene (PS)-PIB-PS (SIBS) is used in the clinical Taxus vascular stent, where it serves as a coating for the physical incorporation of paclitaxel (PTX). [1][2][3] In this application, PTX serves as an anti-proliferative agent that prevents restenosis, the postoperative recurrance of arterial narrowing. [4][5][6] A variety of synthetic approaches have been developed for functionalizing the terminus of PIB with moieties such as halogens, 7,8 thiols, 9 sulfonates, 10 amines, 7 silanes, 11 alcohols, 8,[12][13][14][15] olefins 16,17 or carboxylic acids.…”
mentioning
confidence: 99%
“…SIBS is a very soft, transparent material resembling silicone rubber, with superior mechanical properties. It is used as a drug-eluting coating of coronary stents [6][7][8]. PIB is not degradable under biological conditions, however, its copolymers can be.…”
mentioning
confidence: 99%
“…Controlled ring-opening polymerization (ROP) of cyclic esters, such as lactide, glycolide, cyclic carbonate, and/or ε-caprolactone (ε-CL), have received significant attention due to the good mechanical properties, degradation behavior and biocompatibility of the resulting polymers [1][2][3]. Polyisobutylene (PIB) has been combined with materials widely used for biomedical applications (polyacrylates and -methacrylates, polysiloxanes, polylactones, polyurethanes, poly(ethylene oxide), and poly (vinyl alcohol)), and some devices that use PIB-based materials are approved by the Food and Drug Administration (FDA) [4][5][6]. One of the most relevant combinations is poly(styrene-b-isobutylene-b-styrene) (SIBS).…”
mentioning
confidence: 99%